Who should be vaccinated first? Comparing vaccine prioritization strategies in Israel and European countries using the Covid-19 Health System Response Monitor - Jonathan Cylus; Dimitra Panteli; Ewout van Ginneken (BMC, 2021)
Abstract The rapid rollout of Israel's vaccination program has led to considerable international interest. In this brief commentary we consider how the criteria for vaccination priority groups differ between Israel and selected European countries. We argue that following the Israeli approach of using broad criteria for prioritization- i.e. having fewer groups and a lower age threshold- could have several beneficial effects, including more manageable logistics and fewer roll out delays, as well as potentially reducing pressure on hospitals. With an increasing supply of vaccines becoming available rapidly in much of Europe, countries could consider following the approach of Israel and adopting broader priority criteria going forward.